Small animal anesthesia and analgesia (Blackwell Pub., 2008)
This book provides concise yet comprehensive information about anesthetic equipment, anesthetic and analgesic drugs and techniques, and monitoring. Particular emphasis is placed on indications and contraindications for drugs and techniques. Anesthesia with concurrent conditions and for chronic pain is also covered. Text boxes in each section contain key points